2010
DOI: 10.1002/j.1681-4835.2010.tb00316.x
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Impact of Information and Communication Technologies (ICTs) on Microenterprises in the Context of Development

Abstract: This paper investigates the impact of information and communication technologies, especially landline and mobile phones, computers, and Internet cafés in facilitating economic growth in the developing world. Data on access to ICTs, as well as business-relevant behaviors and attitudes, was collected by a multi-stage probability sample of women microentrepreneurs in Mumbai, India. Main findings include evidence that in urban microenterprises owned by women, business growth is a function of ICT access and is rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 43 publications
2
26
0
Order By: Relevance
“…Chew et al (2010) find that the more positive a female entrepreneur feels about her status and power because of her business venture, the more motivated she will be to make use of ICT for business purposes. The five men are slightly higher adopters of mobile ICT than the five women we have interviewed, reflecting the findings of Chew et al (2010) to some extent. Certain female entrepreneurs seem to rely heavily on what their husbands think and decide concerning ICT.…”
Section: Medium Adoptermentioning
confidence: 94%
See 4 more Smart Citations
“…Chew et al (2010) find that the more positive a female entrepreneur feels about her status and power because of her business venture, the more motivated she will be to make use of ICT for business purposes. The five men are slightly higher adopters of mobile ICT than the five women we have interviewed, reflecting the findings of Chew et al (2010) to some extent. Certain female entrepreneurs seem to rely heavily on what their husbands think and decide concerning ICT.…”
Section: Medium Adoptermentioning
confidence: 94%
“…Steyn (2011) notes that South African MEs prefer to use mobile phones to communicate with their suppliers as well as customers; and found that more than 70% of the entrepreneurs in could use their mobile phones to connect to the internet. However, only a small portion of the mobile's capabilities are currently being used ( Chew et al, 2010;Donner, 2007;Ilavarasan & Levy, 2012). Molony (2009) for instance finds that successful Tanzanian MEs only use their mobile devices to call suppliers or to text clients with delivery information.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations